Synthesis and properties of heterobimetallic rhodium complexes featuring LiI, CuI or ZnII as a Lewis acidic metalloligand. Issue 31 (13th July 2018) - Steinhoff, Patrick; Steinbock, Ralf; Friedrich, Anna; Schieweck, Benjamin G.; Cremer, Christopher; Truong, Khai-Nghi; Tauchert, Michael E.
Abstract : Coordination of Lewis acidic metalloligands Li I, Cu I and Zn II shows a remarkable impact on the CO stretching band in heterobimetallic rhodium complexes. Abstract : A series of [(PMP)Rh(CO)Cl] n + complexes was synthesised and the impact of the metalloligands Cu I, Li I and Zn II on the CO stretching band was analysed.